2022
DOI: 10.1002/bbb.2393
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of triticale anaerobic digestion in a double cropping system: Relation between biomass yield, chemical composition, and biomethane production

Abstract: For sustainable biomethane production, energy crops should not compete for land against feed and food. In response to this requirement, a set of practices for an innovative way to produce food and biomethane was developed in Italy with the Biogasdoneright™ model, which introduces the double‐cropping system along with digestate fertilization and minimum tillage. Triticale is a promising feedstock as energy crop in such systems. Ninteen varieties of triticale harvested at milk and dough development stages were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…In response to this requirement, the Biogasdoneright™ model, based on the doublecropping system along with digestate fertilization and minimum tillage, was proposed. Triticale varieties were evaluated in such a bioenergy production system, and it was found that it is a suitable energy crop for biomethane production [22].…”
Section: Triticale Production In Italy and Destination Of Usementioning
confidence: 99%
“…In response to this requirement, the Biogasdoneright™ model, based on the doublecropping system along with digestate fertilization and minimum tillage, was proposed. Triticale varieties were evaluated in such a bioenergy production system, and it was found that it is a suitable energy crop for biomethane production [22].…”
Section: Triticale Production In Italy and Destination Of Usementioning
confidence: 99%
“…In these production situations, triticale allows a satisfactory biomass to be obtained, in terms of quantity and quality, thus providing a good response to fertilization with organic N and catching nitrogen leaching from the soil during autumn and winter [9,20,21]. Garuti et al [22] reported that the cellulose content and degradability mainly affect the methane production of different triticale cultivars. Furthermore, to increase both the sustainability and profitability of intensive cereal cropping systems for methane production, it is important to introduce genetic and agronomic innovations that are able to enhance their productivity and efficiency, without any significant increase in the cultivation costs.…”
Section: Introductionmentioning
confidence: 99%